Implementing Reciprocal Teaching Strategy to Improve Students’ Reading Comprehension of Narrative Text at Grade XI Science One of SMA Handayani Pekanbaru - Ardiya Ardiya (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2018)
The purposes of this research are to find out whether Reciprocal teaching strategy can improvestudents’ comprehension of narrative text and to find out what factors that influence theimprovement of students’ reading comprehension of narrative text by implementing Reciprocalteaching strategy. The research was a classroom action research which was conducted in twocycles consisting of eight meetings. The research was done from March 17th to April 11th, 2012.There were thirty eight students of Grade XI Science One of SMA Handayani Pekanbaru, andone collaborator treated as participants of this research. The data of the research were takenfrom reading tests, observation, field notes and interviews. The data were analyzed byquantitative and qualitative technique. The study revealed that the implementing of four stepsof Reciprocal teaching (predicting, questioning, clarifying and summarizing) can help thestudents in comprehending the narrative text. Students’ score increased after they applied fourways and they were able to master all indicators of reading comprehension of narrative textconsisting of theme, orientation, complication, and resolution as well as draw conclusion. Thefactors that influenced the change of students’ reading comprehension of narrative text were theparticipation of students, classroom setting and reading materials used in the process of thisresearch. The researcher concludes that Reciprocal teaching can better improve students’reading comprehension of narrative text at the Grade XI Science one of SMA HandayaniPekanbaru.